2017
DOI: 10.1016/j.trecan.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

JARID1 Histone Demethylases: Emerging Targets in Cancer

Abstract: JARID1 proteins are histone demethylases that both regulate normal cell fates during development and contribute to the epigenetic plasticity that underlies malignant transformation. This H3K4 demethylase family participates in multiple repressive transcriptional complexes at promoters and has broader regulatory effects on chromatin that remain ill-defined. There is growing understanding of the oncogenic and tumor suppressive functions of JARID1 proteins, which are contingent on cell context and the protein iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 130 publications
(153 reference statements)
1
65
0
6
Order By: Relevance
“…Convincing documents demonstrated that histone demethylases involve in different cellular procedures such as carcinogenesis, cell fate selection, and cell differentiation [120][121][122]. Currently, the increasing trend of documents showed the essential contribution of histone demethylases such as JARID1, KDM4, LSD1, KDM6B, KDM6A, KMD3, KDM5, and Jumonji domain-consisting of protein 6 (JMJD6) to the cancer stem cell phenotype in several kinds of cancers [61,[123][124][125][126][127][128][129][130]. JMJD6 has been represented as a new molecular modulator of OCSCs [61].…”
Section: Epigenetic Regulators and Oral Cancer Stem Cells Histone Demmentioning
confidence: 99%
“…Convincing documents demonstrated that histone demethylases involve in different cellular procedures such as carcinogenesis, cell fate selection, and cell differentiation [120][121][122]. Currently, the increasing trend of documents showed the essential contribution of histone demethylases such as JARID1, KDM4, LSD1, KDM6B, KDM6A, KMD3, KDM5, and Jumonji domain-consisting of protein 6 (JMJD6) to the cancer stem cell phenotype in several kinds of cancers [61,[123][124][125][126][127][128][129][130]. JMJD6 has been represented as a new molecular modulator of OCSCs [61].…”
Section: Epigenetic Regulators and Oral Cancer Stem Cells Histone Demmentioning
confidence: 99%
“…They are overexpressed in a number of different cancers including breast, ovarian and lung, and their expression correlates with both proliferation rate and propensity for metastatic invasion (HAYAMI et al 2010;HOU et al 2012;TENG et al 2013;YAMAMOTO et al 2014;WANG et al 2015;FENG et al 2017;HUANG et al 2018). The link between the X-linked KDM5C gene and cancer is less straight-forward, as it has both oncogenic and tumor suppressive activities in tissue-dependent manner (HARMEYER et al 2017). The Y-linked KDM5D gene is a tumor suppressor and prognostic indicator of poor outcome in cases of prostate cancer (KOMURA et al 2016;LI et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…CPI-455 inhibits to similar extents KDM5A, B and C [18]. In agreement with a key role for KDM5 histone-demethylases in cancer progression and drug tolerance, KDM5A and KDM5B are up-regulated in many cancers, including gastric, breast and lung cancers as well as acute myeloid leukemia reviewed in [19,20].KDM5A or KDM5B up-regulation appears as a key event in the development of drug tolerance in cancer cells [18, 21] [22, 23].Replication stress (RS), referring to any hindrance to progression of the replication fork during Sphase, has been proposed to be an early step of carcinogenesis by triggering genome instability.The generation of aberrant replication fork structures containing single stranded DNA activates the RS response, primarily mediated by the kinase ATR (ATM--and Rad3--related) and its downstream effector, Chk1. This results in S--phase arrest in order to allow replication stress resolution and fork restart.…”
mentioning
confidence: 53%
“…CPI-455 inhibits to similar extents KDM5A, B and C [18]. In agreement with a key role for KDM5 histone-demethylases in cancer progression and drug tolerance, KDM5A and KDM5B are up-regulated in many cancers, including gastric, breast and lung cancers as well as acute myeloid leukemia reviewed in [19,20].…”
mentioning
confidence: 56%